2015
DOI: 10.1038/gim.2014.75
|View full text |Cite
|
Sign up to set email alerts
|

Differences in BRCA counseling and testing practices based on ordering provider type

Abstract: Purpose To assess potential differences in genetic counseling (GC) services delivered by board certified genetic healthcare providers (GHPs) versus non-GHPs, we evaluated: 1) patient recall and content of pre-test GC for hereditary breast and ovarian cancer; and 2) whether full BRCA1 and 2 gene sequencing was performed when less expensive single-site or Ashkenazi Jewish (AJ) founder mutation testing may be sufficient. Methods Participants completed a questionnaire and provided BRCA test reports that included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…However, previous studies have shown that medical students and non-genetics physicians may not have the genetics knowledge that is considered important for healthcare providers, nor are they comfortable ordering genetic tests (Baars et al 2005;Douma et al 2015;Marzuillo et al 2013;Salm et al 2014). This raises concerns about the quality of patient care that may be provided by nongenetics professionals (Bonadies et al 2014;Cragun et al 2014;Vadaparampil et al 2014). Unfortunately, GCs, the individuals specifically trained to interpret and communicate complex genetic results, are leaving the clinical field.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…However, previous studies have shown that medical students and non-genetics physicians may not have the genetics knowledge that is considered important for healthcare providers, nor are they comfortable ordering genetic tests (Baars et al 2005;Douma et al 2015;Marzuillo et al 2013;Salm et al 2014). This raises concerns about the quality of patient care that may be provided by nongenetics professionals (Bonadies et al 2014;Cragun et al 2014;Vadaparampil et al 2014). Unfortunately, GCs, the individuals specifically trained to interpret and communicate complex genetic results, are leaving the clinical field.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Due to the limited number of cancer genetic counselors in the United States and their geographic concentration in urban areas, traditional genetic counseling by such providers has been inaccessible for some women (Kinney et al, 2014; Lynch et al, 2014; McDonald, Lamb, Grillo, Lucas, & Miesfeldt, 2014; National Society of Genetic Counselors, 2014a). Possibly in response to this and other logistical barriers (e.g., reimbursement, timeliness of scheduling), more non-geneticist physicians have been independently ordering BRCA1/2 testing, which may or may not be accompanied by appropriate pre- and post-test genetic counseling (Bellcross et al, 2011; Cragun et al, 2015; Vadaparampil, Scherr, Cragun, Malo, & Pal, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The utility of genetic counseling in facilitating BRCAmut testing is also becoming more widely recognized, and strategies are being developed to better integrate genetic counseling into the BRCAmut testing practice. A questionnaire survey of 3628 women referred for BRCAmut testing in the United States in 2011–2012 showed that those who received genetic counseling demonstrated greater knowledge, understanding and satisfaction than those who did not .…”
Section: Discussionmentioning
confidence: 99%